Characterization of Biosynthetic Enzymes for Ectoine as a Compatible Solute in a Moderately Halophilic Eubacterium, Halomonas elongata - Ono, Hisayo (American Society for Microbiology, 1999)
1,4,5,6-Tetrahydro-2-methyl-4-pyrimidinecarboxylic acid (ectoine) is an excellent osmoprotectant. The biosynthetic pathway of ectoine from aspartic β-semialdehyde (ASA), in Halomonas elongata, was elucidated by purification and characterization of each enzyme involved. 2,4-Diaminobutyrate (DABA) aminotransferase catalyzed reversively the first step of the pathway, conversion of ASA to DABA by transamination with l-glutamate. This enzyme required pyridoxal 5′-phosphate and potassium ions for its activity and stability. The gel filtration estimated an apparent molecular mass of 260 kDa, whereas molecular mass measured by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was 44 kDa. This enzyme exhibited an optimum pH of 8.6 and an optimum temperature of 25°C and had K(m)s of 9.1 mM for l-glutamate and 4.5 mM for dl-ASA. DABA acetyltransferase catalyzed acetylation of DABA to γ-N-acetyl-α,γ-diaminobutyric acid (ADABA) with acetyl coenzyme A and exhibited an optimum pH of 8.2 and an optimum temperature of 20°C in the presence of 0.4 M NaCl. The molecular mass was 45 kDa by gel filtration. Ectoine synthase catalyzed circularization of ADABA to ectoine and exhibited an optimum pH of 8.5 to 9.0 and an optimum temperature of 15°C in the presence of 0.5 M NaCl. This enzyme had an apparent molecular mass of 19 kDa by SDS-PAGE and a K(m) of 8.4 mM in the presence of 0.77 M NaCl. DABA acetyltransferase and ectoine synthase were stabilized in the presence of NaCl (>2 M) and DABA (100 mM) at temperatures below 30°C.